Greece needs a strategy for its transition to an innovation economy - Alexander S. Kritikos (DIW Economic Bulletin, 2014)
Although Greece is showing initial signs of recovering from its 2008 crash, its economy continues to suffer. It has become clear that the economy will not become prosperous only by the given recommendations of the so called Troika, namely by cutting costs and public expenditures, and by making institutional reforms, as much as these steps are needed. If nothing else changes, the country will have a steady, tourism-based economy supplemented by a food manufacturing base. However, these components will not yield substantial prosperity increases for the Greek society. At the same time the country has a number of unexploited hidden assets, in particular a small number of excellent research institutes and a great number of top researchers, most of them however working abroad. The central problem is the lack of an innovation-oriented industry structure and of a well-functioning innovation system connecting research output with the demand of entrepreneurs and high-tech start-ups in Greece. Greece needs a strategy for a strong capacity building towards the creation of new applied research institutes. If appropriate research networks are developed out of these and if innovative firms result, creating new products with high value-added, the country has the opportunity to transform into an innovation-driven economy.
Keywords: L2; L26; O3; O4; 330; Innovation; Greece; Growth Strategy; Entrepreneurship; Innovation Systems; Regulatory Environment